Changing patterns of ministerial circulation: the Italian case in a long-term perspective. Issue 6 (2nd November 2017) - Martocchia Diodati, Nicola; Verzichelli, Luca
Abstract: The circulation of the ruling class has been a relevant concern in political analysis, but investigation of the determinants of a successful career still remains relatively neglected. This article aims at filling this interpretative gap by focusing on long-term transformations of ministerial careers in Italy. By using an original dataset on ministerial careers between 1976 and 2015, the article explains the patterns of intra-governmental career by analysing the selection for higher government offices. A first descriptive analysis leads to the formulation of a working proposition based on the increasing complexity of the patterns of governmental careers. In this context, the new role of the Prime Minister as a principal in the process of ministerial selection and other procedural constraints are discussed. An ordinal logistic regression analysis confirms the validity of such a general proposition, highlighting the relevance of personalisation and policy expertise in the evolution of intra-governmental careers.